Validation of indices for assessing seismic vulnerability of multi-storeyed buildings with typical vertical irregularities using push-over analysis - Reddy, C. Rudra Srinivasa; Sengupta, Amlan K. (Journal of Structural Engineering, 2025)
Assessment of seismic vulnerability of reinforced concrete buildings can be carried out by various approaches. In this paper, an approach based on push-over analysis was used for generating vulnerability indices. The indices quantify the deficiencies in lateral load resistance and lateral drift of a building, the performance ranges of the hinges formed in the beams and columns, and the inter-storey drift. First, a regular mid-rise building was analysed to evaluate the vulnerable indices. The modelling and analyses were performed using SAP 2000. Next, variations of the building with typical vertical irregularities were studied. It was observed that for the buildings with soft and weak storey or vertical geometric irregularity or in-plane discontinuity in the vertical elements of the lateral load resisting system, the indices based on the performance of columns in a storey and the storey drift ratio showed the maximum deficiency. It was concluded that the indices can indeed be used to identify such typical deficiencies in existing buildings.